A Technique for Peripheral Compartment First and Periportal Access for Hip Arthroscopy - Edward R. Floyd, M.D.; Tanner L. Kippes, B.S.; Kyler A. Hardie, B.S.; Nathan W. Skelley, M.D. (Arthroscopy Techniques)
Hip arthroscopy has become the preferred method for surgical management of numerous hip pathologies. Traditionally, arthroscopic access to the hip has mainly been performed by starting in the central compartment first, which commonly requires capsulotomy and subsequent closure to access the hip joint. This technique is both technically challenging and has been associated with iatrogenic damage to the hip cartilage, as well as the labrum, potentially compromising the integrity of the hip capsule. In this Technical Note, we present our approach to hip arthroscopy that accesses the hip through the peripheral compartment first, with minimal periportal capsulotomies, using a post-less traction bed. This technique can decrease the risk of iatrogenic damage, decrease surgical time, and improve visualization and accessibility for both novice and advanced hip arthroscopy surgeons.